Interlaboratory study for ASTM A1081 Standard Test Method for Evaluating Bond of Seven-Wire Steel Prestressing Strand - Polydorou, Thomaida; Riding, Kyle A.; Peterman, Robert J. (My University, 2014)
ASTM A1081 Standard Test Method for Evaluating Bond of Seven-Wire Steel Prestressing Strand was developed to provide a simple index test for determining the strand bond characteristics of prestressing strand for acceptance and quality control. An interlaboratory study that included nine laboratories was performed to quantify the test method precision and bias, and provide information on challenges faced by laboratories in running the test. Strand from three sources was tested in the interlaboratory study using two different procedures. The first procedure was the test method as adopted by ASTM A1081. The second test method used was a modified version that requires the mortar flow fall in a narrower range of 105-120 instead of 100- 125 as required in ASTM A1081, no time window for performing the test, and a prescribed water to cement ratio of 0.45. The results showed that the changes suggested to ASTM A1081 were able to reduce the coefficient of variation from 14.5 to 11%.
Keywords: Precision; Bias; Standard Test for Strand Bond